Peran Komunikasi dan Kolaborasi Matematika Dalam Pengembangan Keterampilan Abad 21 - Tamara Tesalonika Simarmata; Sari Enjelina Sirait; Tesalonika Br. Sinulingga; Siti Affifah Khoirul Muslim (Penerbit Yayasan Daarul Huda Kruengmane, 2023)
The importance of 21st-century skills in education has become the primary focus in preparing students to face a rapidly changing world. This article explores the critical role of mathematical communication and collaboration in the development of 21st-century skills and presents research methods and findings that support this perspective. The research was conducted through an experimental study involving the participation of elementary school students, which included the implementation of mathematical communication and collaboration strategies in their everyday math learning. The research results indicate a significant improvement in students' abilities in critical thinking, creativity, problem-solving, and communication and collaboration skills. This research concludes that the integration of mathematical communication and collaboration into the curriculum can provide substantial benefits in developing the much-needed 21st-century skills.